The Cornucopia of Intestinal Chemosensory Transduction - Bertrand, Paul P. (Frontiers in Neuroscience, 2009)
The chemosensory transduction mechanisms that the gastrointestinal (GI) tract uses to detect chemical and nutrient stimuli are poorly understood. The GI tract is presented with a wide variety of stimuli including potentially harmful chemicals or toxins as well as 'normal' stimuli including nutrients, bacteria and mechanical forces. Sensory transduction is at its simplest the conversion of these stimuli into a neural code in afferent nerves. Much of the information encoded is used by the enteric nervous system (ENS) to generate local reflexes while complementary information is sent to the central nervous system (CNS) via afferents or by release of hormones to affect behaviour. This review focuses on the chemosensory transduction mechanisms present in the GI tract. It examines the expression and localisation of the machinery for chemosensory transduction. It summarises the types of cells which might be involved in detecting stimuli and releasing neuroactive transmitters. Finally, it highlights the idea that chemosensory transduction mechanisms in the GI tract utilise many overlapping and complementary mechanisms for detecting and transducing stimuli into reflex action.